ijee 2023
DOI: 10.48165/ijee.2023.59125
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Soil Health Card Scheme on Soil Fertility and Crop Production Among the Adopted Farmers

Abstract: The study was conducted in Bareilly district of western UP regarding adoption of recommendation of soil health card scheme and its impact on productivity and economics of different crops i.e. wheat, paddy and sugarcane. It was found that only 40 per cent farmers owned soil health card. However, due to adoption of SHT based fertilizer recommendations there was a significant increase in crop yields of wheat (30.80%), paddy (29.80%) and sugarcane (32.90%). In addition, the adoption of SHT based fertilizer recomme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A remarkable change of 9.38 per cent (3 q/ha) from 32 (before) to 35 q/ha (after) in the yield of wheat was observed after adoption of SHC recommendation by SHC holders in cultivation of wheat [11]. After adoption of SHC recommendations in cultivation of wheat an average farmer found to be decreased expenditure on manurefertilizers and pesticidesherbicides, by 2.33 and 26.62 per cent respectively, while the expenditure on labour (8.21%) and seed (7.25%) increased; with the result of this the total variable cost of cultivation increased by 3.30 per cent from ₹ 40046.17 to 41367.06 per ha and net return increased by 38.19 per cent from ₹ 29363.83 to 40577.94 per ha.…”
Section: Impact Of Shc Scheme On Yield and Incomementioning
confidence: 98%
“…A remarkable change of 9.38 per cent (3 q/ha) from 32 (before) to 35 q/ha (after) in the yield of wheat was observed after adoption of SHC recommendation by SHC holders in cultivation of wheat [11]. After adoption of SHC recommendations in cultivation of wheat an average farmer found to be decreased expenditure on manurefertilizers and pesticidesherbicides, by 2.33 and 26.62 per cent respectively, while the expenditure on labour (8.21%) and seed (7.25%) increased; with the result of this the total variable cost of cultivation increased by 3.30 per cent from ₹ 40046.17 to 41367.06 per ha and net return increased by 38.19 per cent from ₹ 29363.83 to 40577.94 per ha.…”
Section: Impact Of Shc Scheme On Yield and Incomementioning
confidence: 98%
“…The findings revealed that vast majority of respondents (81.67%) know about the significance of soil testing. They were also aware about soil testing laboratories (79.17%), soil moisture before sowing of crops (79.17%), crops suitable for your soil (74.17%), soil types (73.33%), expenditure on crop production decreases after soil testing (72.5%) supported by Singh et al [10], suitable time for collection of soil sample (71.67%), when soil sample should be tested (68.33%), moisture retention capacity of soil (67.50%). Furthermore, respondents were knowledgeable about fertility status of their soil (64.17%), options of crops increased after soil testing (60.83%), knows the difference between soil structure and soil texture (60%), proper depth & weight of soil sample (59.17%), salinity/sodicity of soil (55.83%) and about various major and micronutrients of soil (51.67%).…”
Section: Awareness Of Farmers About Soil Characteristicsmentioning
confidence: 99%
“…Kumar et al [11] in their research paper found that farmers who received soil health cards demonstrated improved nutrient management practices, leading to enhanced crop yields and reduced environmental impact. Singh and Singh [12] reported that the scheme has increased farmers' awareness about soil health and nutrient management practices. The Soil Health Card Scheme has played a crucial role in promoting sustainable agriculture and the efficient use of resources.…”
Section: Soil Health Card Schemementioning
confidence: 99%